4(2x+5)+2(x+3)=-4

Simple and best practice solution for 4(2x+5)+2(x+3)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+5)+2(x+3)=-4 equation:


Simplifying
4(2x + 5) + 2(x + 3) = -4

Reorder the terms:
4(5 + 2x) + 2(x + 3) = -4
(5 * 4 + 2x * 4) + 2(x + 3) = -4
(20 + 8x) + 2(x + 3) = -4

Reorder the terms:
20 + 8x + 2(3 + x) = -4
20 + 8x + (3 * 2 + x * 2) = -4
20 + 8x + (6 + 2x) = -4

Reorder the terms:
20 + 6 + 8x + 2x = -4

Combine like terms: 20 + 6 = 26
26 + 8x + 2x = -4

Combine like terms: 8x + 2x = 10x
26 + 10x = -4

Solving
26 + 10x = -4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + 10x = -4 + -26

Combine like terms: 26 + -26 = 0
0 + 10x = -4 + -26
10x = -4 + -26

Combine like terms: -4 + -26 = -30
10x = -30

Divide each side by '10'.
x = -3

Simplifying
x = -3

See similar equations:

| 4y-5+y+46=5y+50-3y | | x/6+9=-5 | | 7(x+2)=4x+17 | | x/5=-1.2 | | 2.5+x=0.76 | | 8+2n-1=6n+16-3n | | 78=4x-2x | | 27-4(5)= | | x+.2=.1 | | -16x=8x-23-3 | | 8m+7=8m+5 | | x^2-1x=110 | | 9u-6/4=u+2/3+17 | | -4(x-2)+2x+7= | | -20/2 | | 0.8(x+90)+0.06x=121 | | 6x+7=13x+7x | | (-7t-10)/(t+9)x1/7 | | 25v^4-40v^2g+64g=0 | | -3/5+8/2 | | 2[n+1]+5=-5n | | 3y-5=2x | | 2x-8/4=-3 | | 4(2)-12+10x=5(2)-2+x | | 70x-2+32=4x | | r^2-3rx-70x^2= | | -x+156=-300+x | | 125v^6+216g^3=0 | | 9-(5-3)=(9-5)-3 | | 9(3a+6)=6(a+37) | | 0.45+0.05(6-x)=.10(-29) | | 25+9+5x=-2-10x |

Equations solver categories